Management of people with venous leg ulcers by Australian general practitioners: An analysis of the national patient‐encounter data. Issue 4 (30th April 2020) - Weller, Carolina D.; Bouguettaya, Ayoub; Britt, Helena; Harrison, Christopher
Abstract: Venous Leg Ulcers cost Australia's healthcare system millions yearly, as they are underdiagnosed, and possibly undertreated. Most Venous Leg Ulcers are seen in general practice. However, it is currently unknown as to what treatment actions are most common in these contexts. Understanding how they are managed in these settings can improve healthcare delivery and patient outcomes. Using cross‐sectional general practitioner patient encounter data collected April 2006 to March 2016 from the Bettering the Evaluation and Care of Health program, a continuous national study of general practice clinical activity in Australia, we aimed to describe the characteristics of venous leg ulcer management by general practitioners in Australia. Among the 972 100 general practitioner‐patient encounters recorded, 3604 (0.34%) involved management of VLU. Male general practitioners managed Venous Leg Ulcers significantly more often than female general practitioners. Most Venous Leg Ulcers were treated via dressings (76%) and/or pharmacological treatments (25.7%), with few patients receiving the best practice treatment of medical compression (2.1%) or referral (4.9%). Patients with new (first visit) Venous Leg Ulcers were more likely to receive pharmacological treatments and to be referred elsewhere, and less likely to receive dressings than patients receiving follow‐up care. There appears to be a large gap between best practice guidelines and actual Venous Leg Ulcers treatments, as referrals and appropriate treatment was low. Further longitudinal studies are needed to determine the effectiveness of care for people with Venous Leg Ulcers who are managed by general practitioners.